Issues on gene flow and germplasm management - Vicente, M. Carmen de (2005)
This publication is the result of extensive discussions within IPGRI that highlighted the need to identify approaches and procedures to manage germplasm and gene flow, whether from traditionally bred or genetically engineered varieties, to effectively conserve plant genetic resources. This publication compiles the contributions of several authors who address the subject of gene flow from a science-based perspective and its implications for germplasm management.